Standardization, functional shift and language change in Basque - Haddican, William (Sociolinguistic Studies, 2005)
This paper presents a quantitative variationist analysis of data collected in sociolinguistic interviews in the Basque town of Oiartzun in an effort to gauge the influence of a generation of language planning efforts on the local Basque vernacular. In particular, this paper makes the following three claims about these processes. First, the data provide strong apparent-time evidence of change in progress toward standard features. For two morphological variables and one lexical variable, young speakers show significantly lower frequencies of nonstandard forms than middle-aged and older speakers. Second, the changing functional distribution of Basque vs. Spanish in Oiartzun also appears to have had an important impact on younger speakers’ speech. In particular, younger speakers show significantly lower frequencies than older speakers for two informal phonological features. This difference plausibly reflects the fact that younger speakers, unlike their elders, have grown up using Basque in high-register domains –especially schools and the media–where these phonological processes are least common. Third and finally, quantitative variation data together with speakers’ metalinguistic comments in sociolinguistic and ethnographic interviews suggests support for Echeverria’s (2000) proposal that masculinity is iconically linked to informal/low-prestige forms through their association with ‘traditional’ rural Basque spheres.